Analysis of methods and assessment criterions of technical state gas-compressor units - Лановий, М.Д. (Proceedings of National Aviation University, 2010)
In the article we have observed perspective methods of diagnostic gas-compressor units at various stages of their maintenance phase and the optimal and informative assessment criterion of their technical state.